2020
DOI: 10.1103/physrevapplied.13.014031
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Constant in the Folding of Thin Viscoelastic Sheets

Abstract: If one folds a thin viscoelastic sheet under an applied force, a line of plastic deformation is formed which shapes the sheet into an angle. We determine the parameters that define this angle experimentally and show that no matter how much load one applies or what is the thickness of the sheet, it is impossible to make angles less than a certain minimum angle in a definite time. Moreover, it is shown that regardless of whether the sheet is released freely afterward or kept under the load, a robust logarithmic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, in both cases, after a brief onset ( t < 1 s) the force relaxation is logarithmic over many decades in time: where C and B are constants. Previously, other molecular and/or athermal disordered systems including creased sheets 26 , 27 , crumpled papers 28 , 29 , and foams 29 were also reported to display such logarithmic mechanical response to deformation. Moreover, enthalpy and specific volume measurements during the aging of polymers show a similar logarithmic behavior 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both cases, after a brief onset ( t < 1 s) the force relaxation is logarithmic over many decades in time: where C and B are constants. Previously, other molecular and/or athermal disordered systems including creased sheets 26 , 27 , crumpled papers 28 , 29 , and foams 29 were also reported to display such logarithmic mechanical response to deformation. Moreover, enthalpy and specific volume measurements during the aging of polymers show a similar logarithmic behavior 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, enthalpy and specific volume measurements during the aging of polymers show a similar logarithmic behavior 30 . In the case of creased polymeric (Mylar and paper) sheets, which contain lines of localized plastic deformations, analysis of the relationship between C and B revealed that the logarithmic process is governed by a constant that doesn’t change with the sheet thickness or the applied load 27 . Similarly, for our polymer spheres, B is proportional to C for the whole range of the squeezing forces, from 0.1 N to above 50 N (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, crumpling often proceeds in an unpredictable manner: As a thin sheet is confined, stresses spontaneously localize to produce a complex network of creases in the sheet [8,9]. To elucidate the mechanisms underlying this complex process, crumpled structures have been investigated at different length scales, from the energy and geometry of individual ridges [10,11,12,13] and vertices [14,15], to the mechanical response of single folds [16,17,18,19], to the collective properties of disordered ridge networks, such as slow relaxation [20,21,22,23,24] and non-monotonic aging [25]. However, more remains to be understood about these rich phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that, although the two transient dynamics occur on very different time scales (2-3 s vs 25,000 s), they are similar when plotted as a function of sliding distance where t 0 → 0 is a singular point in time from which the interfacial system evolves by aging and rejuvenation. Such a singular behavior arises in all disordered systems demonstrating logarithmic aging, ranging from creased/crumpled paper [25,26] and granular piles [27] to static frictional interfaces [7,12,28]. The consequence is that, if t 0 → 0 , the first term of Eq.…”
mentioning
confidence: 99%